Kinetic and Analytical Studies of Oxidation of Tannic Acid with Ammonium Hexanitratocerate(IV) in Nitric Acid Medium. - CHAUDHARI, U.R.; MADHAVA RAO, B. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of tannic acid is extensively studied at various temperatures to evaluate the thermodynamic parameters and the formation constant (Kƒ) of the intermediate complex and furthermore to achieve the optimal conditions for analytical determination of tannic acid. In view of these facts the formation constant, Kƒ, and the other thermodynamic parameters evaluated in these investigations can be considered as a total measure of [Ce(IV)-glucose] complex, [Ce(IV)-gallic acid] complex and [Ce(IV)-unhydrolysed tannic acid] complex. Second order rate constants obtained in these investigations are utilised to correlate the effects of variation of [tannic acid], [Ce(IV)], [H+], aNO3 – and added [Ce(III)]. The mechanism of oxidation of tannic acid involves the formation of a transitory intermediate cyclic complex followed by disproportionation of the complex. The disproportionation or the intermediate complex is the rate determining step. The values for Kƒ, ΔE≠, -ΔH≠, ΔF≠, ΔS≠ and log A are found to be 2.456 x 104 lit mol–1, 11.21 kcal mole–1, 11.32 kcal mole–1, -6.19 kcal mole–1, -16.68 e.u. and 7.669 sec–1 respectively.